Effects of greater economic integration within the European Community on the United States: third followup report (USITC Washington, D.C.US)
Covers the period since July 1, 1990. Highlights anticipated changes in the EC and potential effects on the United States. Also focuses on implications of EC market integration for GATT, the Uruguay Round, and other international commitments. Includes a discussion of the effects of the EC92 program on the U.S. value-added telecommunication and information services industry.
DC